Immobilization of Horseradish Peroxidase onto Montmorillonite/Glucosamine–Chitosan Composite for Electrochemical Biosensing of Polyphenols - Piccoli, María Belén; Gulotta, Florencia Alejandra; Montenegro, Mariana Angélica; Vanden Braber, Noelia Luciana; Paz Zanini, Verónica Irene; Ferreyra, Nancy Fabiana (2024)
Impact Factor: 4.9 (2023); 5-Year Impact Factor: 5.2 (2023).